2010
DOI: 10.1093/aob/mcq096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temporal heterogeneity of water supply on the growth of Perilla frutescens depend on plant density

Abstract: Competition for water probably makes plants more sensitive to the water heterogeneity. In addition, the intensity of intraspecific competition can be affected by the temporal patterns of water supply. Because both resource heterogeneity and intraspecific competition affect resource acquisition and growth of plants, their interactive effects should be evaluated more carefully under future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 19 publications
4
32
0
Order By: Relevance
“…However, in nature, plants are generally exposed to competition with their neighbors. Thus, extrapolating the real meaning of findings obtained from individual species is difficult (Bloor et al, 2008 have confirmed that both intra- (Hagiwara et al, 2010) and interspecific (Blank, 2010) competition are likely to affect the response of each species to climate change. However, no clear pattern in the outcome of interspecific and intraspecific competition has been found in high mountain trees under elevated temperature.…”
Section: Introductionmentioning
confidence: 85%
“…However, in nature, plants are generally exposed to competition with their neighbors. Thus, extrapolating the real meaning of findings obtained from individual species is difficult (Bloor et al, 2008 have confirmed that both intra- (Hagiwara et al, 2010) and interspecific (Blank, 2010) competition are likely to affect the response of each species to climate change. However, no clear pattern in the outcome of interspecific and intraspecific competition has been found in high mountain trees under elevated temperature.…”
Section: Introductionmentioning
confidence: 85%
“…Nutrient levels must be considered in the study of water heterogeneity for three reasons: (1) nutrient availability depends on water availability (Lambers et al 1998); (2) plants will be more sensitive to variability in water supply under nutrientrich than under nutrient-poor conditions, because they grow larger and require more water when nutrients are abundant (Goldberg and Novoplansky 1997;Stevens et al 2006); and (3) nutrient levels affect the root growth of plants (Fitter 1997), and this consequently can affect water uptake. In fact, an interactive effect of water heterogeneity and nutrient levels has been reported in the annual herbaceous species Perilla frutescens L. (Hagiwara et al 2008(Hagiwara et al , 2010. A few agricultural studies have also showed the interaction of water heterogeneity and nutrient levels (Silber et al 2003;Xu et al 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Few studies have investigated the effects of population density on plant responses to water heterogeneity. In P. frutescens, however, water heterogeneity affects plant growth more clearly at high population densities than at low densities (Hagiwara et al 2010). Because the insight on the independent effects of water heterogeneity has been increasing recently (Fay et al 2003;HeislerWhite et al 2008), and because the independent effects of nutrient levels and population densities on plant growth have been well studied (Begon et al 2006), the interactive effects of water heterogeneity with nutrient levels and/or population densities should be investigated in turn.…”
Section: Introductionmentioning
confidence: 99%
“…Plant responses to water frequency vary depending on nutrient availability and soil water content [3][6]. Soil water status also affects soil biota [7], and interacts with soil biota to affect plant growth.…”
Section: Introductionmentioning
confidence: 99%